THE CORRELATION BETWEEN LEARNER AUTONOMY AND ENGLISH PROFICIENCY OF INDONESIAN EFL COLLEGE LEARNERS - I Putu Ngurah Wage Myartawan; Mohammad Adnan Latief; Suharmanto Suharmanto (TEFLIN, 2013)
The present study aimed to investigate the correlation between learner autonomy psychologically defined in the study as a composite of behavioral intentions to do autonomous learning and self-efficacy in relation to autonomous learning, and English proficiency. The sample comprised 120 first semester English-majored students of a state university in Bali, Indonesia. The data were collected from documents and by administering two questionnaires. Multiple linear regression analysis conducted revealed that learner autonomy and English proficiency as defined in the study had a significant, strong, positive relationship. Some suggestions related to the results of the study, especially in the EFL context, are discussed.Â